TO EVALUATE THE EFFECTIVENESS OF VARIOUS METHODS OF PLASTIC SURGERY OF POST-TRAUMATIC DEFECTS OF THE CRANIAL VAULT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Target The present work is a study of the significance of clinical and neurologicalsymptoms and an assessment of the effectiveness of using various methods of plastic surgery forpost-traumatic defects of the cranial vault.